2004
DOI: 10.1142/s0218127404010485
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Thermal Displacements in Modular Tool Systems

Abstract: There is an important interest in compensating thermally induced errors of modular tool systems to improve the manufacturing accuracy. In this paper, we test the hypothesis whether we can predict such thermal displacements by using a nonlinear regression analysis, namely the alternating conditional expectation algorithm (ACE [Breiman & Friedman, 1985]), reliably. The data analyzed were generated by two different finite element spindle models of modular tool systems. As the main result, we find that the ACE-alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The maximal correlation and optimal transformation approach were applied recently to nonlinear dynamic systems to identify delay in lasers [35] and partial differential equations in fluid dynamics [37]. The ACE algorithm turned out to be a very efficient tool for nonlinear data analysis [16,35,39,43,44]. …”
Section: Model-based Data Analysismentioning
confidence: 99%
“…The maximal correlation and optimal transformation approach were applied recently to nonlinear dynamic systems to identify delay in lasers [35] and partial differential equations in fluid dynamics [37]. The ACE algorithm turned out to be a very efficient tool for nonlinear data analysis [16,35,39,43,44]. …”
Section: Model-based Data Analysismentioning
confidence: 99%
“…These approaches on the one hand aim at modeling one or more regulation processes, and on the other hand provide model parameters which should be used to answer clinically relevant questions. In this tutorial we have introduced an approach which is very promising in data-driven modeling and modelbased data analysis [Wessel et al, 2000b;Wessel et al, 2004a;Wessel et al, 2004b;Wessel et al, 2006]. We have found that the maximal correlation method is a powerful tool for medical data analyses and for solving mechanical engineering problems.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the result less sensitive to the data distribution. The maximal correlation and optimal transformation approach have recently been applied to nonlinear dynamical systems especially to model river flow data [Chen & Tsay, 1993], to identify delay in lasers [Voss & Kurths, 1997] and partial differential equations in fluid dynamics , to predict thermal displacements in modular tool systems [Wessel et al, 2004a;Wessel et al, 2004b] and to medical data analyses [Wessel et al, 2000b;Wessel et al, 2006]. A more general review on nonlinear system identification is given in .…”
Section: Nonlinear Model Based Data Analysismentioning
confidence: 99%